AKUMULASI ENDAPAN KUARTER SEBAGAI RESPON ATAS GERAK-GERAK TEKTONIK DI DAERAH KAMPUNG DUREN, KABUPATEN BANGKA SELATAN, PROPINSI BANGKA-BELITUNG - -, Herman Moechtar; -, Suyatman Hidayat (Bulletin of Scientific Contribution, 2009)
The study of Quaternary deposits was conducted using analyses of sedimentology and stratigraphy of thirteen boreholes obtained along the west to the east traverse, which was approximately parallel to the valley of Duren river, not far from the Duren Village between Bikang and Gadung villages, District of South Bangka, Province of Bangka-Belitung. The depth of each borehole varies from 2.20 to 30.10 m.Studies on Quaternary deposits revealed five facies which represented, encompassing alluvial fan (FKa), river channel (FAs), floodplain (FDb), lake/lacustrine (FDn), and swamp (FRw) depositional environments. Based on the result of correlation of the lateral and vertical variation of the facies, four intervals of the deposition (IP I-IV) were recognised. Each of the interval exhibits the variation of the depositional environment under the control of tectonic and climatic changes. The tectonic activities and climatic changes which controlled the deposition were recorded as four episode stages. These respective episodes were, (1) dry climate with tectonic effects, (2) sub humid climate which was influenced by fault in the west, (3) humid to sub-humid climate which was followed by active of the three faults on the basin, and (4) dry climate without being influenced by tectonics.